2017
DOI: 10.1016/j.jhep.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition in cholangiocarcinoma: From clinical evidence to regulatory networks

Abstract: Cholangiocarcinoma (CCA) is an aggressive tumor with a poor prognosis due to its late clinical presentation and the lack of effective non-surgical therapies. Unfortunately, most of the patients are not eligible for curative surgery owing to the presence of metastases at the time of diagnosis. Therefore, it is important to understand the steps leading to cell dissemination in patients with CCA. To metastasize from the primary site, cancer cells must acquire migratory and invasive properties by a cell plasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 144 publications
3
122
0
Order By: Relevance
“…On the other hand, epithelial-to-mesenchymal transition (EMT) plays an important role in primary tumor progression and metastasis, and this process is characterized by loss of epithelial and acquisition of mesenchymal characteristics of tumor cells [3133]. During EMT progression, the expression levels of mesenchymal markers and matrix metalloproteinases (MMPs) are increased, in contrast, epithelial adhesion of molecules are decreased, as previously reported [24,34].…”
Section: Resultsmentioning
confidence: 82%
“…On the other hand, epithelial-to-mesenchymal transition (EMT) plays an important role in primary tumor progression and metastasis, and this process is characterized by loss of epithelial and acquisition of mesenchymal characteristics of tumor cells [3133]. During EMT progression, the expression levels of mesenchymal markers and matrix metalloproteinases (MMPs) are increased, in contrast, epithelial adhesion of molecules are decreased, as previously reported [24,34].…”
Section: Resultsmentioning
confidence: 82%
“…86 This process is observed during embryonic development, wound healing and cancer metastasis. 87 Since the tumor cells are transported by bloodstream and their diffusion is dependent upon vessels, increased angiogenesis in tumor results in augmentation of metastasis and spread of cancer cells. 88 It has been suggested that tumor endothelial cells (TECs) are involved in the survival, proliferation and metastasis of cancer cells.…”
Section: The Role Of Vessel In Metastasismentioning
confidence: 99%
“…8 Studies have suggested that EMT is a complexed and well-coordinated process, in which the extracellular signal molecules, transcription factors, miRNAs, epigenetic and posttranslational regulation all play critical roles. 9,10 The transforming growth factor-β (TGF-β) as an EMT-induction factor induces EMT through a variety of signal pathways as well as the classical TGFβ-Smad pathway. Activated Smads combine with Smad4 to regulate the transcription of many TGF-β/Smad target genes such as E-cadherin.…”
mentioning
confidence: 99%